VD_FINDINFO AVS 47/11 - 56/2014 vom 16. Dezember 2014 - VD Tribunal cantonal (2014)
COTISATION PARITAIRE, AVS, CAISSE DE COMPENSATION{AVS/AI}, MESURE D'INSTRUCTIONASSURANCE SOCIALE | 319 CO, 16 al. 1 LAVS, 52 LAVS